1992
DOI: 10.1111/j.1939-165x.1992.tb00584.x
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Ferritin Assay for Canine Sera

Abstract: An improved serum ferritin assay for canine serum has been developed. It uses two monoclonal antibodies in a sandwich arrangement. Serum ferritin can be determined on undiluted canine sera with this assay. The recovery of ferritin added to canine serum ranged from 98 to 106%, the within-assay coefficient of variability was 3.3 to 4.5%, and the assay-to-assay variability was 9.8 to 10.2%. Serum ferritin from 61 apparently healthy dogs had a geometric mean of 252 ng/ml, with a range of 80 ng/ml to 800 ng/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 9 publications
2
23
0
1
Order By: Relevance
“…This attests to both the reproducibility of the assay and the stability of frozen ferritin. The within-assay variability and assay-to-assay variabilities were comparable to those observed with other monoclonal antibody-based ferritin assays [Weeks et al, 1988;Andrews et al, 1992Andrews et al, , 1994.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This attests to both the reproducibility of the assay and the stability of frozen ferritin. The within-assay variability and assay-to-assay variabilities were comparable to those observed with other monoclonal antibody-based ferritin assays [Weeks et al, 1988;Andrews et al, 1992Andrews et al, , 1994.…”
Section: Discussionsupporting
confidence: 77%
“…However, the finding that anti-equine ferritin antibodies cross react with rhinoceros ferritin, and the subsequent development of an ELISA test to measure serum ferritin in the rhinoceros [Smith et al, 1995] led us to investigate whether we could develop an assay to measure fur seal ferritin using murine monoclonal antibodies previously raised to canine ferritin [Andrews et al, 1992].…”
Section: Introductionmentioning
confidence: 99%
“…As técnicas para a determinação da ferritina sérica são reações dirigidas por anticorpos, como radioimunoensaio, ELISA, imunoturbidimetria e quimioluminescência, de alta sensibilidade. Os reagentes comerciais de ELISA para a dosagem de ferritina sérica em cães já foram desenvolvidos nos Estados Unidos (WEEKS et al, 1988;ANDREWS et al, 1992) e no Japão (WATANABE et al, 2000), no entanto, não são comercializados, devido ao custo elevado para a produção inviabilizando sua exportação.…”
Section: Introductionunclassified
“…The values indicate the means measured in triplicate, and the error bars show standard deviation. concentrations determined previously in normal dogs by Andrews [1] and Watanabe [14] were 252 ng/ml (n=61, 80-800 ng/ml) and 479 ng/ml (n=51, 298-959 ng/ml), respectively. The values reported in this study are obviously much higher.…”
mentioning
confidence: 99%
“…From past reports, detection of serum ferritin in dogs has been accomplished by sandwich enzyme-linked immunosorbent assays (ELISAs) using a mouse anti-canine ferritin monoclonal antibody, and purified canine liver ferritin as the standard [1]. However, it has been reported that in canine serum an autoantibody exists that binds to ferritin.…”
mentioning
confidence: 99%